Alloleptosphaeria shangrilana sp. nov. and first report of the genus (Leptosphaeriaceae, Dothideomycetes) from China - Thiyagaraja, Vinodhini; Wanasinghe, Dhanushka N.; Karunarathna, Samantha C.; Tennakoon, Danushka S.; Hyde, Kevin D.; To-Anun, Chaiwat; Cheewangkoon, Ratchadawan (Phytotaxa, 2021)
Alloleptosphaeria shangrilana, collected from dead wood of a dicotyledonous host in Shangri-La, China, is introduced as a new species based on evidence from morphological data and DNA sequence analyses. Maximum likelihood and Bayesian analyses of combined SSU, LSU and ITS sequence data were used to clarify the phylogenetic affinity of the new species. The new taxon is characterized by semi-immersed to superficial ascomata, a thick peridium, branched and septate pseudoparaphyses, cylindrical asci, muriform ascospores and overlapping uniseriate ascospores. Alloleptosphaeria species have been reported from England, Italy, Thailand and this is the first report of the genus in China. A detailed morphological description and analyses of the phylogenetic results are given for the new species. A key and synopsis table to the genus are also provided.